Economic impact of tank rehabilitation in rainfed region of India - T M, Kiran Kumara; Kumar, Shiv; S, Aditya K; Singh, Dharam Raj; Immanuelraj, Kingsly; Kallega, Harish Kumar; Singh, Prem Lata (The Indian Journal of Agricultural Sciences, 2020)
The present investigation measures economic impact of tanks restoration on productivity and income of 240 farm households in rainfed region of India. The detailed information was collected with designed questionnaire for the period 2017–18 from farm households using tank irrigation in two districts in the state of Andhra Pradesh. Propensity score matching technique was employed to assess the impact of tank rehabilitation. Findings revealed that restoration of tanks leads to an improvement in production and livelihood of tank water users in the study area. Yield and income of rice crop is increased by a magnitude of 0.54–0.62 tonne/ha and ₹6045/ha to ₹8278/ha respectively. Study suggests that to achieve food security and to mitigate the scarcity of water, restoration of tanks is inevitable for rainfed regions. Further, recasting such protocols and replicating similar models to other regions not only enhance the sustainable agricultural production but also improve livelihoods of millions of small and marginal farmers in the country.